A low-trap state perovskite solar cell and preparation method thereof

By using tetramethyl ammonium hexafluorophosphate in perovskite solar cells for ion exchange, forming composite compounds, the problem of trap state in interface layer in perovskite solar cells is solved, the charge transport and stability are improved, and high Perovskite solar cells with efficiency and thermal stability.

CN113871536BActive Publication Date: 2025-01-07NINGBO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111119199.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-24
Publication Date
2025-01-07
Estimated Expiration
2041-09-24

AI Technical Summary

Technical Problem

Due to the limitations of the production technology, perovskite solar cells have defect traps between the internal and interface layers of perovskites, resulting in carrier capture and reducing device performance.

Method used

Tetramethyl ammonium hexafluorophosphate is used to ion exchange at the bottom of the perovskite polycrystalline film to form a composite compound, reduce the trap state at the interface between the electron transport layer and the perovskite polycrystalline film, reduce the potential difference, and trigger crystals through the modification layer. Grid expansion improves the crystallinity and stability of perovskite polycrystalline film.

Benefits of technology

Effectively reduce the non-radiative recombination of carriers at the interface, promote charge transmission, and improve the battery efficiency and stability of perovskite solar cells. The battery efficiency reaches the highest value of 21.43%, and remains high under high temperature or high humidity conditions. Thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113871536B_ABST
    Figure CN113871536B_ABST
Patent Text Reader

Abstract

The invention discloses a low-trap state perovskite solar cell and a preparation method thereof, comprising a conductive glass layer, an electron transport layer, a modification layer, a perovskite polycrystalline film, a hole transport layer and a metal electrode layer arranged in layers in sequence, wherein the modification layer is a compound formed after tetramethylammonium hexafluorophosphate is subjected to ion exchange at the bottom of the perovskite polycrystalline film. Tetramethylammonium hexafluorophosphate is subjected to ion exchange at the bottom of the perovskite polycrystalline film to form a composite compound, which reduces the trap state at the interface between the electron transport layer and the perovskite polycrystalline film, thereby reducing the energy offset of the interface, reducing the potential difference between the electron transport layer and the perovskite polycrystalline film, thereby reducing the non-radiative recombination of carriers at the interface, and facilitating charge transfer. After the ion exchange, the lattice expansion of the modification layer and the perovskite polycrystalline film is also triggered, the grain size of the corresponding perovskite polycrystalline film is increased, and the crystallinity and stability of the perovskite polycrystalline film are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to a low-trap state perovskite solar cell and a preparation method thereof, belonging to perovskite solar cells. [Background technology]

[0002] Compared with traditional monocrystalline silicon solar cells, as well as new thin-film solar cells such as dye-sensitized solar cells and organic solar cells, perovskite solar cells are conducive to future industrialization and can meet more abundant market demands due to their advantages such as simple preparation methods, diverse processes, low cost, and the ability to prepare flexible devices. In addition, perovskite materials themselves have long carrier diffusion lengths, suitable band gaps, and low exciton binding energies, and are highly valued by scientific research and industry. Perovskite materials have been used in solar cells since 2009, with an initial efficiency of 3.8%. Until recently, the photoelectric efficiency has reached 25.5%, and the development has been extremely rapid, creating history in the photovoltaic field. Unfortunately, although perovskite solar cells are an ideal choice for the next generation of photovoltaic devices, due to the current preparation technology constraints, the perovskite light absorption layer film is basically a polycrystalline film, which inevitably leads to defect traps between the perovskite interior and the interface layer, which will capture carriers, resulting in reduced device performance, and even affecting the performance of the device. [Summary of the invention]

[0003] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a low-trap state perovskite solar cell and a preparation method thereof.

[0004] To solve the above technical problems, the present invention adopts the following technical solutions:

[0005] A low-trap state perovskite solar cell comprises a conductive glass layer, an electron transport layer, a modification layer, a perovskite polycrystalline film, a hole transport layer and a metal electrode layer which are arranged in layers in sequence, wherein the modification layer is a compound formed by ion exchange of tetramethylammonium hexafluorophosphate at the bottom of the perovskite polycrystalline film.

[0006] The beneficial effects of the present invention are:

[0007] Tetramethylammonium hexafluorophosphate forms a composite compound by ion exchange at the bottom of the perovskite polycrystalline film. The composite compound reduces the trap state at the interface between the electron transport layer and the perovskite polycrystalline film, thereby reducing the energy offset of the interface and the potential difference between the electron transport layer and the perovskite polycrystalline film, thereby reducing the non-radiative recombination of carriers at the interface, which is beneficial to charge transport. After ion exchange, the lattice expansion of the modified layer and the perovskite polycrystalline film is also triggered, and the grain size of the corresponding perovskite polycrystalline film is increased, and the crystallinity and stability of the perovskite polycrystalline film are significantly improved.

[0008] The material of the perovskite polycrystalline film of the present invention is FAPbI3.

[0009] A method for preparing a low-trap state perovskite solar cell comprises the following steps:

[0010] Step S1: preparing an electron transport layer on the conductive glass layer;

[0011] Step S2: preparing a tetramethylammonium hexafluorophosphate solution and a perovskite precursor solution, spin-coating the tetramethylammonium hexafluorophosphate solution onto the electron transport layer, and directly spin-coating the perovskite precursor solution after the tetramethylammonium hexafluorophosphate solution is spin-coated, followed by annealing to form a modified layer and a perovskite polycrystalline film;

[0012] Step S3: sequentially preparing a hole transport layer and a metal electrode layer on the surface of the perovskite polycrystalline film.

[0013] The solvent components of the tetramethylammonium hexafluorophosphate solution and the perovskite precursor solution of the present invention are the same.

[0014] The preparation method of the tetramethylammonium hexafluorophosphate solution of the present invention is as follows: dissolving tetramethylammonium hexafluorophosphate in a mixed solvent of DMF and DMSO and stirring the mixture to obtain a 10 mg / ml tetramethylammonium hexafluorophosphate solution.

[0015] The preparation method of the perovskite precursor solution of the present invention is as follows: FAI and PbI2 are mixed and dissolved in a mixed solvent of DMF and DMSO at a molar ratio of 1:1 to form a FAPbI3 precursor solution with a concentration of 1.4M, MAI and PbBr2 are mixed and dissolved in a mixed solvent of DMF and DMSO at a molar ratio of 1:1 to form a MAPbIBr2 precursor solution with a concentration of 1.4M, and 300 microliters of the FAPbI3 precursor solution, 15 microliters of the MAPbIBr2 precursor solution and 8 mg of MACl powder are mixed to form a perovskite precursor solution.

[0016] The entire process of step S2 of the present invention is carried out in a nitrogen atmosphere.

[0017] In step S2 of the present invention, the spin coating time of the tetramethylammonium hexafluorophosphate solution is 30 seconds and the rotation speed is 5000 rpm, and the spin coating time of the perovskite precursor solution is 30 seconds and the rotation speed is 4000 rpm.

[0018] The electron transport layer of the present invention is made of tin dioxide.

[0019] Other features and advantages of the present invention will be disclosed in detail in the following specific embodiments and drawings.

Brief Description of the Drawings

[0020] The present invention will be further described below in conjunction with the accompanying drawings:

[0021] Figure 1 The XPS graph (O1s) of tin dioxide in Comparative Example 1 and Example 1 of the present invention;

[0022] Figure 2 The XPS graph (F1s) of TMAPF6 in Comparative Example 1 and Example 1 of the present invention;

[0023] Figure 3 The mixed solution of FAPbI3 and DMSO before and after adding tetramethylammonium hexafluorophosphate 1 H NMR spectra;

[0024] Figure 4 The mixed solution of tetramethylammonium hexafluorophosphate and DMSO before and after adding FAPbI3 19 F NMR spectra;

[0025] Figure 5 FTIR graphs of tetramethylammonium hexafluorophosphate, Comparative Example 1 of the present invention and Example 1;

[0026] Figure 6 The XRD intensity of PbI2 in Comparative Example 1 and Example 1 of the present invention changes with time;

[0027] Figure 7 The normalized UV-vis absorption intensity of the perovskite polycrystalline film in Comparative Example 1 and Example 1 of the present invention changes with time (600nm);

[0028] Figure 8 The normalized UV-vis absorption intensity of the perovskite polycrystalline film in Comparative Examples 1, 3, 4 and Example 1 of the present invention changes with time (600nm);

[0029] Fig. 9 The XRD intensity of PbI2 in Comparative Examples 1, 3, 4 and Example 1 of the present invention changes with time;

[0030] Fig.10 IPCE curves of the solar cells in Comparative Example 1 and Example 1 of the present invention;

[0031] Fig.11 1 is the efficiency stability curve of the solar cell in comparative example 1 and example 1 of the present invention;

[0032] Fig.12 It is a statistical diagram of efficiency distribution of solar cells in comparative example 1 and example 1 of the present invention. [Specific implementation method]

[0033] The technical solutions of the embodiments of the present invention are explained and described below in conjunction with the drawings of the embodiments of the present invention, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work are all within the protection scope of the present invention.

[0034] In the following description, terms such as "inside", "outside", "up", "down", "left", "right", etc. that indicate directions or positional relationships are only used to facilitate the description of the embodiments and simplify the description, and do not indicate or imply that the referred device or element must have a specific direction, be constructed and operate in a specific direction. Therefore, it should not be understood as a limitation of the present invention.

[0035] Comparative Example 1:

[0036] This comparative example provides a method for preparing a perovskite solar cell, comprising the following steps:

[0037] Step S1: dilute a commercially available 150 mg / ml aqueous solution of tin dioxide nanoparticles with deionized water, and filter after magnetic stirring for 4 hours to obtain a 30 mg / ml aqueous solution of tin dioxide nanoparticles, and then spin-coat it on the conductive glass layer. The spin-coating time is 30 seconds, the rotation speed is 4000 rpm, and the solution is dried at 150° C. for 30 minutes to obtain an electron transport layer.

[0038] Step S2: FAI and PbI2 are mixed and dissolved in a mixed solvent of DMF and DMSO (volume ratio 4:1) at a molar ratio of 1:1 to form a FAPbI3 precursor solution with a concentration of 1.4M, MAI and PbBr2 are mixed and dissolved in a mixed solvent of DMF and DMSO (volume ratio 9:1) at a molar ratio of 1:1 to form a MAPbIBr2 precursor solution with a concentration of 1.4M, 300 microliters of FAPbI3 precursor solution, 15 microliters of MAPbIBr2 precursor solution and 8 mg of MACl powder are mixed to form a perovskite precursor solution, and the perovskite precursor solution is spin-coated onto the electron transport layer (second spin coating, the first spin coating time is 5s, the rotation speed is 1000rpm, the second spin coating time is 30s, and the rotation speed is 4000rpm), chlorobenzene is added dropwise as an anti-solvent during the spin coating process, and then annealed at 150°C for 15min to form a perovskite polycrystalline film;

[0039] Step S3: Spin-coat a chlorobenzene solution of Spirio-OMeTAD (1 M concentration, doped with 4-TBP, lithium salt, FK209) onto the perovskite polycrystalline film at a rotation speed of 3000 rpm for 30 seconds to form a hole transport layer on the surface of the perovskite polycrystalline film, and then evaporate a 60 nm thick silver electrode layer on the surface of the hole transport layer.

[0040] The perovskite solar cell obtained in this comparative example includes a conductive glass layer, an electron transport layer, a perovskite polycrystalline film, a hole transport layer and a silver electrode layer which are arranged in layers in sequence.

[0041] Embodiment 1:

[0042] This embodiment provides a method for preparing a low-trap state perovskite solar cell. The difference between this method and Comparative Example 1 is that there is a step S2' between step S1 and step S2.

[0043] Specifically, step S2': dissolve tetramethylammonium hexafluorophosphate in a mixed solvent of DMF and DMSO (volume ratio 4:1) and stir to obtain a 50mM tetramethylammonium hexafluorophosphate solution. After step S1, transfer the electron transport layer to a glove box, and spin-coat the tetramethylammonium hexafluorophosphate solution onto the electron transport layer under a nitrogen atmosphere, with a spin coating time of 30s and a rotation speed of 5000rpm. This process does not require drying and annealing.

[0044] After step S2' is completed, step S2 is directly performed. Accordingly, during the annealing process of step S2, a modified layer and a perovskite polycrystalline film are simultaneously formed.

[0045] Therefore, the perovskite solar cell finally obtained in this embodiment includes a conductive glass layer, an electron transport layer, a modification layer, a perovskite polycrystalline film, a hole transport layer and a silver electrode layer arranged in layers in sequence.

[0046] First, during the spin coating of the perovskite precursor solution in step S2, although most of the solvent of the tetramethylammonium hexafluorophosphate solution on the surface of the electron transport layer has evaporated, annealing has not yet been performed, so the interface between the top of TMAPF6 and the bottom of FAPbI3 is mutually soluble. In the subsequent annealing process, the mutually soluble tetramethylammonium hexafluorophosphate (TMAPF6) and FAPbI3 can undergo a certain degree of ion exchange, thereby forming a layered (TMA) at the interface. x FA 1-x Pb(PF6) x I 3-x , while the lower part of the modified layer is still TMAPF6, and the TMAPF6 at the lower part of the modified layer does not form contact with FAPbI3. Since the solvent composition of the tetramethylammonium hexafluorophosphate solution and the perovskite precursor solution is the same, it can effectively promote the mutual dissolution process of TMAPF6 and FAPbI3 at the interface.

[0047] Embodiment 2:

[0048] The difference between this embodiment and embodiment 1 is that in step S2', the concentration of the tetramethylammonium hexafluorophosphate solution is 100 mM.

[0049] Embodiment 3:

[0050] The difference between this embodiment and embodiment 1 is that in step S2', the concentration of the tetramethylammonium hexafluorophosphate solution is 150 mM.

[0051] Comparative Example 2:

[0052] The difference between this embodiment and comparative embodiment 1 is that tetramethylammonium hexafluorophosphate is additionally added to the perovskite precursor solution, and the mass fraction of tetramethylammonium hexafluorophosphate in the final perovskite precursor solution is 3%.

[0053] The photoelectric data of comparative examples 1 and 2 and examples 1, 2 and 3 are shown in Table 1. The test equipment is Keithley 4200, Newport solar simulator 3A, and the test conditions are AM1.5, 100 mW / cm 2 .

[0054] Table 1

[0055] <![CDATA[Jsc(mA / cm 2 )]]> Voc(V) FF(%) PCE(%) Comparative Example 1 24.83 1.05 74.1 19.32 Example 1 25.2 1.1 77.3 21.43 Example 2 23.32 1.01 68.4 16.12 Example 3 21.72 0.94 56.7 11.57 Comparative Example 2 21.06 0.84 52.3 9.25

[0056] It can be seen from Table 1 that with the increase of the concentration of tetramethylammonium hexafluorophosphate solution, the short-circuit current Jsc, open-circuit voltage Voc and fill factor FF of the battery first increase and then decrease, and in Example 1, the short-circuit current Jsc, open-circuit voltage Voc and fill factor FF reach the maximum value at the same time. Correspondingly, in Example 1, the battery efficiency reaches the highest value of 21.43%.

[0057] The reasons are as follows:

[0058] See also Figure 3 The mixed solution of FAPbI3 and DMSO has a broad peak at 8.8ppm, which is caused by FA + After adding TMAPF6, the peak of HN in the sample splits into two, located at 8.9 and 8.6 ppm, respectively. This indicates that PF6 - and FA + New hydrogen bonds are formed between them. The peak positions of F in the mixed solution of TMAPF6 and DMSO are at -70.84 and -69.33 ppm. After adding FAPbI3, the peak positions of F shift to -70.81 and -69.3 ppm. This proves that (TMA) x FA 1- x Pb(PF6) x I 3-x PF6 - F and FA +The HN in the interface forms hydrogen bonds, which enhances the overall thermal stability and phase stability of the solar cell. At the same time, it increases the defect formation energy at the interface and reduces the energy loss at the interface.

[0059] See also Figure 1 When the electron transport layer is made of tin dioxide, the binding energy of the electron transport layer O1s decreases slightly after the modification layer is prepared. The reason is that part of the TMA + and will react with O in SnO2 2- Combine. Figure 2 After TMAPF6 was spin-coated onto the electron transport layer, the core binding energy of F1s in TMAPF6 also shifted. The reason is that F has a strong electronegativity and binds to Sn on the SnO2 surface. 4+ Combine;

[0060] See also Figure 5 In Comparative Example 1, TMA + The peak of CN is at 1491cm -1 , while in Example 1 the peak position shifted to 1471 cm -1 , it can be seen that TMA + Ion exchange also occurred with FAPbI3.

[0061] In summary, compared with directly spin-coating FAPbI3 onto SnO2, setting TMAPF6, TMA + and PF6 - At the same time, it forms a strong chemical bond with FAPbI3 and tin dioxide, which can enhance the bonding strength between FAPbI3 and tin dioxide and form an energy level transition between FAPbI3 and tin dioxide.

[0062] But it is also worth noting that TMA + The ionic radius is Greater than FA + The ionic radius PF6 - The ionic radius is Greater than I - The ionic radius This makes (TMA) x FA 1-x Pb(PF6) x I 3-x The lattice of is expanded compared to that of FAPbI3. x FA 1-x Pb(PF6) x I 3-xThe tolerance factor t1 of (x=0.05) is calculated to be 0.989, and the tolerance factor t2 of FAPbI3 is calculated to be 0.987. t1 is slightly larger than t2, indicating that (TMA) x FA 1-x Pb(PF6) x I 3-x The octahedral structure of TMA is more unstable than that of FAPbI3. + and PF6 - From the perspective of crystal expansion, it is not conducive to the stability of the perovskite structure.

[0063] Under high temperature conditions, the phase transition of FAPbI3 is suppressed, and humidity mainly causes the decomposition of FAPbI3. Figure 6 , the perovskite polycrystalline film in Comparative Example 1 and Example 1 was first placed in a nitrogen environment at 85°C for 48 hours, and then placed under 85°C and 60% humidity conditions for 24 hours. The XRD intensity of lead iodide obtained by decomposing the perovskite polycrystalline film in Comparative Example 1 and Example 1 increased with time. Under a nitrogen environment, the decomposition rate of the perovskite polycrystalline film of Example 1 is slower than that of the perovskite polycrystalline film of Comparative Example 1, but the decomposition rates of the two are not much different. When switched to 60% humidity conditions, the decomposition rates of the perovskite polycrystalline film in Comparative Example 1 and Example 1 both increased, but the decomposition rate of the perovskite polycrystalline film in Example 1 did not increase much, and the decomposition rate of the perovskite polycrystalline film in Comparative Example 1 increased greatly, which caused a huge gap between the decomposition rates of the perovskite polycrystalline film in Comparative Example 1 and Example 1. It can be seen from this that the hydrogen bond between FAPbI3 and TMAPF6 can effectively inhibit the diffusion and decomposition of organic ions at the bottom interface of FAPbI3, and offset the adverse effects caused by crystal expansion, so that the perovskite polycrystalline film has good thermal stability.

[0064] Under high temperature or high humidity conditions, MAPbI3 mainly decomposes. In contrast, under room temperature and high humidity conditions, FAPbI3 mainly undergoes phase transition and decomposes very little. Figure 7 , the perovskite polycrystalline film in Comparative Example 1 and Example 1 was placed in an extremely humid environment at 30°C and over 90% RH. After 16 hours, the perovskite polycrystalline film in Comparative Example 1 had turned seriously yellow, and the absorption intensity was only about 30% of the initial state, while the perovskite polycrystalline film in Example 1 remained black, and the absorption intensity was still about 70% of the initial state. It can be seen that the bottom modification of TMAPF6 can effectively inhibit the transformation of FAPbI3 from α phase to δ phase.

[0065] In addition, in Examples 2 and 3, due to the excessive modification of TMAPF6, TMA + and PF6 -It will accumulate in large quantities at the grain boundaries, hindering charge transfer and even offsetting the advantages of the aforementioned hydrogen bonds, causing the battery efficiency to gradually decrease.

[0066] The perovskite precursor solution contains a small amount of MAPbIBr2 and MACl, and MA + The ionic radius is smaller than FA + Ionic radius, MA in the nucleation process of perovskite crystals + It will serve as a nucleation center to form a perovskite phase. In Comparative Example 2, TMAPF6 is directly doped into FAPbI3, and TMA with a larger ionic radius + This process is disturbed, causing the battery efficiency in Comparative Example 2 to be much lower than that in Examples 1-3 and Comparative Example 1, and relying on hydrogen bonding is completely unable to compensate for the above adverse effects. In contrast, Examples 1-3 use TMAPF6 as the bottom interface of the perovskite, which effectively dilutes the influence of the above ionic radius and highlights the role of hydrogen bonding.

[0067] In contrast, Example 1 adopts the method of FAPbI3 bottom modification, which can effectively avoid TMA + and PF6 - Entering the perovskite grain boundaries, limiting TMA + and PF6 - The effect range of perovskite. In addition, the (TMA) generated at the interface x FA 1-x Pb(PF6) x I 3-x It effectively reduces the generation of trap states, promotes carrier transport at the interface, and reduces non-radiative recombination.

[0068] See also Fig.10 It can be seen that in the range of 300-850nm, the IPCE of Example 1 is almost completely higher than that of Comparative Example 1. The bottom layer modification of FAPbI3 by TMAPF6 has a certain degree of absorption enhancement effect on light of various wavelengths, thereby increasing the integrated current density from 23.74mA / cm 2 Increased to 24.72mA / cm 2 .

[0069] See also Fig.11 , under the conditions of 25°C and 30% RH, the battery in Example 1 still retains nearly 90% of the initial efficiency after 1200h, while the battery in Comparative Example 1 only has about 50% of the initial efficiency. It can be seen that the improved thermal stability and phase stability brought by TMAPF6 greatly enhance the efficiency stability of FAPbI3.

[0070] In order to further verify the credibility of TMAPF6 in improving battery efficiency, 30 groups of samples were prepared for Example 1 and Comparative Example 1. Fig.12 It can be seen that the efficiency of the 30 groups of samples in Comparative Example 1 is between 17.5% and 19.25%, while the efficiency of the 30 groups of samples in Example 1 is between 19.25% and 21.5%. This shows that TMAPF6 can effectively and stably improve the battery efficiency.

[0071] To further verify the TMA + and PF6 - For the synergistic effect of FAPbI3 bottom layer modification, additional comparisons of Comparative Examples 3 and 4 were performed.

[0072] Comparative Example 3:

[0073] The difference between this comparative example and Example 1 is that the 50 mM tetramethylammonium hexafluorophosphate solution is replaced by a 50 mM TMAI solution.

[0074] Comparative Example 4:

[0075] The difference between this comparative example and Example 1 is that the 50 mM tetramethylammonium hexafluorophosphate solution is replaced by a 50 mM HPF6 solution.

[0076] For comparison purposes, the photoelectric data of Comparative Examples 1, 3, 4 and Example 1 are shown in Table 2. The test conditions of Comparative Examples 3 and 4 are consistent with those of Comparative Example 1.

[0077] Table 2

[0078] <![CDATA[Jsc(mA / cm 2 )]]> Voc(V) FF(%) PCE(%) Comparative Example 1 24.83 1.05 74.1 19.32 Example 1 25.2 1.1 77.3 21.43 Comparative Example 3 24.05 0.99 65.7 15.65 Comparative Example 4 24.54 1.03 71.5 18.09

[0079] It can be seen that modifying the bottom layer of FAPbI3 with TMAI and HPF6 respectively not only fails to improve the battery efficiency, but will reduce the battery efficiency.

[0080] See also Figure 8 and 9 The thermal stability and phase stability of the perovskite polycrystalline films in Comparative Example 3 and Comparative Example 4 were tested. The test methods and test conditions were the same as those in Figure 7 and Figure 6 It can be seen that for thermal stability, regardless of TMA + and PF6 - , the bottom modification of FAPbI3 has been improved to a certain extent, and the effects of the two are similar. - The lifting effect is slightly higher than TMA + Improvement effect, but TMA in Example 1 + and PF6 -The synergistic effect shows that the thermal stability of the perovskite polycrystalline film is not between that of Comparative Example 3 and Comparative Example 4, but is significantly improved compared with Comparative Example 3 and Comparative Example 4. - It also has a positive effect on the perovskite polycrystalline film, but TMA + The single action is not conducive to the perovskite polycrystalline film. The reason may be that no hydrogen bond is formed at the bottom of the perovskite polycrystalline film in Comparative Example 3. More importantly, TMA + and PF6 - Under the synergistic effect, the phase stability of the perovskite polycrystalline film in Example 1 is improved compared with Comparative Example 3 and Comparative Example 4.

[0081] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.

Claims

1. A low-trap state perovskite solar cell, characterized in that: The invention comprises a conductive glass layer, an electron transport layer, a modification layer, a perovskite polycrystalline film, a hole transport layer and a metal electrode layer which are arranged in layers in sequence. The modification layer is a compound formed by ion exchange of tetramethylammonium hexafluorophosphate at the bottom of the perovskite polycrystalline film.

2. The low trap state perovskite solar cell according to claim 1, characterized in that: The material of the perovskite polycrystalline film is FAPbI3.

3. A method for preparing a low-trap state perovskite solar cell, characterized in that: The steps include: Step S1: preparing an electron transport layer on the conductive glass layer; Step S2: preparing a tetramethylammonium hexafluorophosphate solution and a perovskite precursor solution, spin-coating the tetramethylammonium hexafluorophosphate solution onto the electron transport layer, and directly spin-coating the perovskite precursor solution after the tetramethylammonium hexafluorophosphate solution is spin-coated, followed by annealing to form a modified layer and a perovskite polycrystalline film; Step S3: sequentially preparing a hole transport layer and a metal electrode layer on the surface of the perovskite polycrystalline film.

4. The method for preparing a low-trap state perovskite solar cell according to claim 3, characterized in that: The solvent composition of the tetramethylammonium hexafluorophosphate solution and the perovskite precursor solution is the same.

5. The method for preparing a low-trap state perovskite solar cell according to claim 4, characterized in that: The tetramethylammonium hexafluorophosphate solution is prepared as follows: tetramethylammonium hexafluorophosphate is dissolved in a mixed solvent of DMF and DMSO and stirred to obtain a 10 mg / ml tetramethylammonium hexafluorophosphate solution.

6. The method for preparing a low-trap state perovskite solar cell according to claim 5, characterized in that: The preparation method of the perovskite precursor solution is as follows: FAI and PbI2 are mixed and dissolved in a mixed solvent of DMF and DMSO at a molar ratio of 1:1 to form a FAPbI3 precursor solution with a concentration of 1.4M, MAI and PbBr2 are mixed and dissolved in a mixed solvent of DMF and DMSO at a molar ratio of 1:1 to form a MAPbIBr2 precursor solution with a concentration of 1.4M, and 300 microliters of the FAPbI3 precursor solution, 15 microliters of the MAPbIBr2 precursor solution and 8 mg of MACl powder are mixed to form a perovskite precursor solution.

7. The method for preparing a low-trap state perovskite solar cell according to claim 6, characterized in that: The entire process of step S2 is carried out in a nitrogen atmosphere.

8. The method for preparing a low-trap state perovskite solar cell according to claim 5, characterized in that: In step S2, the spin coating time of tetramethylammonium hexafluorophosphate solution is 30 seconds and the rotation speed is 5000 rpm, and the spin coating time of perovskite precursor solution is 30 seconds and the rotation speed is 4000 rpm.

9. The method for preparing a low-trap state perovskite solar cell according to claim 3, characterized in that: The electron transport layer is made of tin dioxide.

Citation Information

Patent Citations

  • Method for passivating perovskite and preparation process of perovskite solar cell

    CN112216799A

  • Method for modifying stannic oxide by ammonium hexafluorophosphate and application of stannic oxide in perovskite solar cell

    CN113421975A